Energy Management System Implementation Strategy in The Concentrating Division of PT Freeport Indonesia Based on ISO 50001:2018 - Adi Yusup Tauruy; Idqan Fahmi; Mukhamad Najib (Business Review and Case Studies, 2022)
This study aims to 1) analyze the current level of energy management system implementation by the PTFI Concentrating Division, 2) analyze the comparison of the Concentrating Division's energy management system with the ISO 50001:2018 standard, 3) formulate a strategy for implementing an energy management system according to the ISO 50001 standard. :2018 at the PT Freeport Indonesia Concentrating Division processing plant. The method in this study uses gap analysis (gap and IPA) and analytical hierarchy process (AHP). The implementation strategy is formulated based on the results of a comparison of the performance level of the energy management system with the 7 clauses of ISO 50001:2018 and their level of importance. The results obtained are 7 clauses that do not meet the standards and 3 clauses of which have a high level of importance but low performance levels to be handled with four different strategies: 1) conducting internal audits and external energy audits, 2) energy management system training, 3) carrying out activities energy efficiency-oriented production, 4) using automation systems and technology on equipment. Keywords: AHP, concentrate processing plant, energy management system, gap analysis, ISO 50001:2018